Chrysin Ameliorates Influenza Virus Infection in the Upper Airways by Repressing Virus-Induced Cell Cycle Arrest and Mitochondria-Dependent Apoptosis - Liu, Ying; Song, Xun; Li, Chenyang; Hu, Hao; Li, Wanlin; Wang, Lu; Hu, Jing; Liao, Chenghui; Liang, Hanbai; He, Zhendan; Ye, Liang (Frontiers in Immunology, 2022)
Chrysin has been proven to possess antiviral properties, but the precise underlying anti-influenza mechanism and its anti-influenza efficacy in vivo are largely unclear. In this study, we investigated the involvement of chrysin in the blockade of cell cycle and apoptosis in distinct cell lines subjected to two H1N1 influenza A virus (IAV) strains, as well as its anti-IAV activity in vivo. Here, we found an early unidentified finding that chrysin strongly impeded IAV replication through a mechanism that was autonomous of innate antiviral immune activation and viral protein interaction. Surprisingly, chrysin can suppress IAV-induced cell cycle arrest in the G0/G1 phase by downregulating the expression levels of P53 and P21 while promoting Cyclin D1/CDK4 and Cyclin E1/CDK2 activation. Furthermore, chrysin dramatically inhibited the IAV-triggered mitochondrial apoptotic pathway by altering the balance of Bax/Bcl-xl and reducing caspase-9 and caspase-3 activation. Accumulated reactive oxygen species (ROS) reduction may contribute to the inhibitory role of chrysin in cell cycle arrest and apoptosis following IAV infection. Notably, chrysin preferably inhibited IAV replication in the upper respiratory tract, indicating that it might be a promising drug for restraining the spread of respiratory viruses.